MILK PROTEINS-DERIVED BIOACTIVE PEPTIDES - Özer KINIK; Oğuz GÜRSOY (Pamukkale University Journal of Engineering Sciences, 2002)
Milk proteins are a source of various biologically active peptides, which are formed enzymatically either by digestive enzymes or during milk fermentation. These peptides have been shown to have different biochemical and physiological effects, such as binding to opioid receptors, inhibition of angiotensin I-converting enzyme (ACE), antimicrobial, antihypertensive, antioxidative, antithrombotic, immunomodulatory and mineral binding effects. This review will focus on chemical structure, physiological properties, production and formation mechanisms in dairy food of milk-derived bioactive peptides and their usage potential as functional food ingredient.